2020
DOI: 10.1021/acs.joc.0c01665
|View full text |Cite
|
Sign up to set email alerts
|

Method for the Large-Scale Synthesis of Multifunctional 1,4-Dihydro-pyrrolo[3,2-b]pyrroles

Abstract: A thorough investigation has enabled the optimization of the synthesis of 1,4-dihydro-pyrrolo[3,2- b ]pyrroles. Although salts of such metals as vanadium, niobium, cerium, and manganese were found to facilitate the formation of 1,4-dihydro-pyrrolo[3,2- b ]pyrroles from amines, aldehydes, and diacetyl, we confirmed that iron salts are the most efficient catalysts. The conditions identified (first step: toluene/AcOH = 1:1, 1 h, 50 °C; second step: toluene/AcOH = 1:1,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
49
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 45 publications
(50 citation statements)
references
References 56 publications
1
49
0
Order By: Relevance
“…Among known heteropentalenes, the pyrrolo[3,2- b ]pyrrole 105,106 core (PP) constitutes the most electron-rich scaffold. We have recently demonstrated that a simple pyrrolo[3,2- b ]pyrrole-based chromophore 51 bearing two peripheral 4-nitrophenyl groups (Fig.…”
Section: Suppressing Intersystem Crossing In Non-polar Solventsmentioning
confidence: 99%
“…Among known heteropentalenes, the pyrrolo[3,2- b ]pyrrole 105,106 core (PP) constitutes the most electron-rich scaffold. We have recently demonstrated that a simple pyrrolo[3,2- b ]pyrrole-based chromophore 51 bearing two peripheral 4-nitrophenyl groups (Fig.…”
Section: Suppressing Intersystem Crossing In Non-polar Solventsmentioning
confidence: 99%
“… 18 In order to install coumarin units into these locations on this heterocycle, formyl-coumarin derivatives were designed for the recently optimized multicomponent reaction between aromatic amines, butane-2,3-dione, and aromatic aldehydes for the pyrrolo[3,2- b ]pyrrole synthesis. 19 The formyl-coumarin derivatives were additionally designed to possess an auxiliary CO 2 Me group at position 3 in order to increase their accepting character. The isomeric 6- and 7-formyl coumarins 2a and 2b designed for this purpose are shown in Scheme 1 .…”
mentioning
confidence: 99%
“…Changes in the UV-Vis-NIR absorption spectra during polarization within the first oxidation peak revealed a decrease in the intensity of the bands at 468, 492 nm (1a) and 495 and 522 nm (1c) 59 ( Fig. 9 ), while the shift of the absorption in the infrared direction of the output bands of 1c indicates a decrease in the energy of the π–π* transition due to a partial localization of the HOMO orbital also on the pyridine rings.…”
Section: Resultsmentioning
confidence: 99%